Production of seed potatoes in Cyprus: the effects of roguing and planting date on the spread of potato leaf roll virus, tuber yield, and infestation by potato tuber moth - Ioannou, Nicolas (My University, 1989)
Field experiments during 1984-6 tested the effects of planting date on the development of aphid infestations and the spread of potato leaf roll virus (PLRV) in rogued or unrogued plots of potatoes, cv. Spunta. Plantings were made each month from December to April, the customary time for planting being February. Aphid infestation in early-planted plots was severe throughout the growing season; plots planted in February were also severely infested early in the growing season but the populations later gradually declined to undetectable levels. Nevertheless, the incidence of PLRV in the latter plots was as high as in those planted in December-January. Late-planted crops escaped aphid infestation and PLRV infection, either in part (March planting) or completely (April planting). Such crops, however, were uneconomical due to poor yields and heavy losses from potato tuber moth infestation. Roguing significantly reduced the spread of PLRV in all years but its interaction with planting date was insignificant.
Keywords: Aphids; Myzus persicae; Phthorimaea operculella; Solanum tuberosum L. cv. Spunta